Thermal Change Affects Flexural and Thermal Properties of Fused Deposition Modeling Poly(Lactic Acid) and Compression Molding Poly(Methyl Methacrylate) - Charasseangpaisarn, Taksid; Wiwatwarrapan, Chairat; Srimaneepong, Viritpon (European Journal of Dentistry, 2022)
Objective Polylactic acid (PLA) is one of the most widely used materials in three-dimensional (3D) printing technology due to its multiple advantages such as biocompatibility and biodegradable. However, there is still a lack of study on 3D printing PLA for use as a denture base material. The goal of this study was to compare 3D printing PLA to traditional poly(methyl methacrylate) (PMMA) as a denture basis.Materials and Methods The PMMA (M) and PLA (L) specimens were fabricated by compression molding, and fuse deposition modeling technique, respectively. Each specimen group was divided into three different temperature groups of 25°C (25), 37°C (37), and 55°C (55). The glass transition temperature (Tg) of raw materials and specimen was investigated using differential scanning calorimetry. The heat deflection temperature (HDT) of each material was also observed.Statistical Analysis The data of flexural strength and flexural modulus were analyzed with two-way analysis of variance, and Tukey honestly significant difference. The Tg and HDT data, on the other hand, were descriptively analyzed.Results The results showed that PLA had lower flexural strength than PMMA in all temperature conditions, while the PMMA 25°C (M25) and PMMA 37°C (M37) obtained the highest mean values. PLA 25°C (L25) and PLA 37°C (L37) had significant higher flexural modulus than the other groups. However, the flexural properties of L55 could not be observed, which may be explained by Tg and HDT of PLA.Conclusion PLA only meets the flexural modulus requirement, although it was greater than flexural modulus of PMMA. On the other hand, PMMA can meet both good flexural strength and modulus requirement. However, increase in temperature could reduce flexural strength and flexural modulus of PMMA and PLA.
Keywords: denture base; flexural modulus; flexural strength; fuse deposition modeling; temperature